The Concept Of Inter-religious Life In The Medina Charter And Nostra Aetate - Tri Yuliana Wijayanti (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The diversity of society gives rise to the diversity of beliefs and religions held by the community. However, unfortunately the progress of people's lives is not followed by the progress of inter-religious relations which cannot be separated from the protracted conflict. Followers of a religion often doubt the purpose of realizing inter-religious harmony initiated by a religion, even though there are two major world religions that both have religious documents that contain the concept of inter-religious life, namely Nostra Aetate (Catholic) and Medina Charter (Islam).This study was structured to answer academic problems, including (1) knowing the concept of inter-religious life in the Medina Charter, (2) knowing the concept of inter-religious life in Nostra Aetate, and (3) comparing the concept of inter-religious life in the two documents. This research, which is classified as comparative religious research and uses a deductive analysis knife. Based on the results of the analysis, it was found that the concept of inter-religious life in the Medina Charter is understood that every individual has the right to freedom of religion and emphasis on inter-religious unity. The concept of inter-religious life in Nostra Aetate contains several points of meaning. As for after the two documents were compared, it was found that the difference lies in the content of the text and the views of other people. The parallel side lies in the goal of the concept of inter-religious life. Further research in historical and linguistic studies will be able to further complement this study.